PENGGUNAAN METODE COMMUNITY BASED MANAGEMENT DALAM PENGELOLAAN ASET WAKAF (TINJAUAN TERHADAP LEMBAGA WAKAF AL-KHAIBAR DAN SABILILLAH KOTA MALANG) - M. Hasan Ubaidillah (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2024)
Waqf is one of the philanthropic endeavours aimed at reducing inequality and equalising human development. In its development, waqf has metamorphosed into productive waqf that can provide economic value to society through modern waqf management methods. This research seeks to provide a comprehensive understanding of the concept and dynamics of waqf, the community-based management method in waqf management, and the use of this method in modern waqf institutions. This research is a social and economic research with a combination of data collection methods, namely through library research and interview methods conducted at two waqf institutions in Malang city. The waqf institutions in question are Al-Khaibar Waqf Institution and Sabilillah Waqf Institution in Malang city. The results of this research are: 1) Waqf is interpreted as holding property that can be taken advantage of by maintaining its original form to be distributed to permissible ways and has undergone many developments, both from the form, management institutions, and content; 2) as for what is meant by community-based management is a pattern of community empowerment centered on community participation based on the organisation; and 3) the application of the CBM method in Malang City waqf institutions is symbiotic hierarchical, with several stages, namely: problem solving, problem analysis, determining goals and objectives, planning, implementation, and evaluation.